The fiscal and equity impact of tax expenditures in the European Union - Salvador Barrios; Francesco Figari; Luca Gandullia; Sara Riscado (European Commission, Joint Research Centre (JRC), 2016)
Tax expenditures are preferential tax treatments granted to specific individuals or categories of households which aim at achieving social and economic goals - poverty and inequality reduction, and employment promotion, among others. Tax expenditures are widely used by EU Member States. However, their fiscal and equity impacts are not always clear and their effectiveness and efficiency as a policy instrument needs to be carefully evaluated, especially in the present context of constrained public finances. Tax expenditures might in some cases distort economic incentives be it towards consumption or investment, in some case by favouring rent seeking behaviour and making tax systems less transparent and/or regressive from a social viewpoint. While policy recommendations often call for streamlining tax expenditures, in practice policy measures are often difficult to design in particular given the difficulty in measuring the fiscal and equity impact of tax expenditures. This paper quantifies the fiscal and equity effects of tax expenditures in 27 European countries making use of EUROMOD, the EU-wide microsimulation model. We focus on four specific categories of preferential tax treatments affecting personal income taxation related to housing, pension, education and health expenditures. One key feature of the microsimulation model EUROMOD is that it embeds the interaction between different tax instruments and benefits entitlement which, in EU tax systems, proves essentially to fully gauge the fiscal and equity impact of tax expenditures. In order to quantify the impact of tax expenditure on governments' tax revenues and on households' disposable income a benchmark tax system scenario is created where tax expenditures - in the form of allowances, deductions, exemptions, reliefs and credits - are explicitly considered. We find a variety of effects, in terms of sign and magnitude, across Member States, and within these, among types of households and across generations. Overall our findings suggest that the impact of tax expenditure on tax revenues and on income inequalities can be sizeable. The redistributive impact of removing tax expenditures can go both directions, either on the progressive or regressive side, depending on the country and the tax expenditure considered. This result points out to the importance of a careful country specific scrutiny, for each type of tax expenditures.
Keywords: 330; Tax expenditures; microsimulation; fiscal and equity impacts